Freedom of Speech and Public Reason - Sadurski, Wojciech (The Oxford Handbook of Freedom of Speech, 2021)
This chapter addresses the salience of the Rawlsian idea of public reason for freedom of speech. It applies a philosophical template of Public Reason to a typically legal issue: what motivations for speech restrictions render the restriction legitimate under the Public Reason criterion, and what motivations taint the law as illegitimate, because they are non-endorsable by reasonable persons to whom they apply. Traces of this pattern of argument can be found in several legal systems: in the United States, Germany, New Zealand, and Australia, when they grapple with constitutionality of restrictions on freedom of speech, and choose the motive path (rather than the effects path) of scrutiny. The most typical pattern of argument is the one which disfavours content-oriented restrictions, as compared to content-neutral restrictions. This distinction offers attractive avenues of argument when it is viewed in the context of legislative motives, and how they fare under a general principle of Public Reason. The chapter then establishes that viewpoint restrictions and subject-matter restrictions—two subcategories of a broader genus of content-based restrictions of freedom of speech—correspond to two perceived wrongful motivations in regulating speech: intolerance and paternalism.